2008
DOI: 10.1152/ajpheart.00318.2008
|View full text |Cite
|
Sign up to set email alerts
|

Sex and limb-specific ischemic reperfusion and vascular reactivity

Abstract: Nishiyama SK, Wray DW, Richardson RS. Sex and limbspecific ischemic reperfusion and vascular reactivity. Am J Physiol Heart Circ Physiol 295: H1100 -H1108, 2008. First published July 11, 2008 doi:10.1152/ajpheart.00318.2008.-With little known regarding sex and limb heterogeneity, we investigated vascular reactivity and ischemic reperfusion (IR) in the upper and lower extremities of 15 healthy men (26 Ϯ 2 yr) and women (23 Ϯ 1 yr). Doppler ultrasound was used to evaluate IR and flow-mediated dilation (FMD) aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…We found that the hyperemic response to transient ischemia is greater and more prolonged in males than in females. It is well documented that gender has a significant impact on POHR readings not only in large arteries but also in the microcirculation of the skin . Our results suggest that in a challenged situation the vasodilator (FMD and ascending dilatation) capacity of the gingival vessels may be higher in males.…”
Section: Discussionmentioning
confidence: 49%
“…We found that the hyperemic response to transient ischemia is greater and more prolonged in males than in females. It is well documented that gender has a significant impact on POHR readings not only in large arteries but also in the microcirculation of the skin . Our results suggest that in a challenged situation the vasodilator (FMD and ascending dilatation) capacity of the gingival vessels may be higher in males.…”
Section: Discussionmentioning
confidence: 49%
“…Indeed, it should be emphasized that a growing body of work from our group (8,(21)(22)(23)47) and others (18,19,24,31,42) has identified a limb specificity in vascular function, including responses to PE (25). Thus recognition that the present study was performed in the leg is essential for interpretation of the present findings and indeed may partially explain the disparity in responses between the present study and prior work in the exercising forearm (6,9).…”
Section: ␣ 1 -Mediated Vasoconstriction During Exercise: Absolute Vsmentioning
confidence: 55%
“…Greater FMD in women is expected [32,33] because of their smaller brachial artery diameter, as FMD is highly dependent upon arterial diameter [33,34]. However, this gender difference is not always observed [35] and may disappear after the menopause [32].…”
Section: Table 3 Univariate Inter-relationships Between Atbf Bmi Andmentioning
confidence: 99%